Meningkatkan Audience (Purpose Awareness) Siswa Sekolah Dasar melalui Kegiatan Menulis yang Berorientasi pada Pembaca dan Tujuan - Utami Widiati; Furaidah Furaidah (Universitas Negeri Malang, 2016)
The study was intended to develop students' audience/purpose awareness in writing through the implementation of audience/purpose-related writing activities. A collaborative-action-research design was employed, involving 2 researchers and 2 elementary school teachers. Thirty three (33) fourth-graders of elementary school participated in the study. Data in the form of students' writings were collected in the first and second terms of the 1999/2000 school year, which were then analyzed quantitatively and qualitatively. The findings suggest that at the end of the second cycle of the action research the students' ability develops, which is indicated in the audience adaptations found in their writings and in the use of appropriate genre and register